Concepción sociocultural del climaterio en Occidente. - Cárdaba García, Rosa María; Cárdaba García, Inés (Cultura de los Cuidados, 2017)
Introduction: Including the sociocultural perspective in the care of women is key to attaining good health. The biomedical model has obviated these factors in the study of climacteric, so that a new female pathology, Climatérico Syndrome, has been created. Main objective: To reflect from the feminist perspective, on the western sociocultural dimension of the climacteric. Methodology: We present an original article of theoretical reflection based on the Feminist Theory of the Holistic Health Paradigm that understands gender as a variable. Conclusions: Other cultures show us a climacteric woman who does not suffer from the signs and symptoms that we find in Western women, which makes us think of the importance of the society of reference as a factor that influences the experience of the climacteric. Menopause marks a turning point in the woman who passes from maturity to senescence through a facilitating rite of passage, but this in the West is diluted and the woman lives this stage in a negative way.